O05.6 Endometrial Gardnerella Vaginalisand Atopobium Vaginea Are Associated with Histologic Endometritis Among Women with Clinically Diagnosed Pelvic Inflammatory Disease (PID). (13th July 2013) - Hillier, S L; Rabe, L K; Meyn, L; Macio, I; Trucco, G; Amortegui, A; Darville, T; Wiesenfeld, H C
Abstract : Objective: While Neisseria gonorrhoeae (GC) and Chlamydia trachomatis (CT) are known to cause PID, many women with clinical signs and symptoms of PID and histologic evidence of endometritis have neither of these pathogens. Our objective was to describe microorganisms in the upper genital tract of women with PID, and to evaluate their association with histologic endometritis. Methods: Women presenting with symptoms and meeting the CDC diagnosis of PID had an endometrial biopsy obtained by Pipelle, and the tissue was split for microbiological and histological assessment. Cultivated microorganisms were identified using phenotypic and genotypic characteristics. Fisher's exact tests were used to assess the association between microorganisms and endometritis (plasma cells ± neutrophils). Results: Of 136 women with clinical PID, 55 (40%) had histologic evidence of endometritis, and endometrial GC and/or CT was associated with endometritis (29% vs. 6%, P < 0.001). In addition to STIs, a broad range of bacteria representing 63 different species were recovered from 53 (39%) of the endometrial biopsy samples, including 8 novel species. The recovery of any non-GC/non-CT organisms from the endometrium was associated with histologic endometritis (53% vs. 30%, P = 0.008). Both G. vaginalis (35% vs. 16%, P = 0.01) and A. vaginae (22% vs. 3%, P < 0.001) were associated with histologic endometritis. Other anaerobic bacteria associated with bacterial vaginosis including Prevotella timonensis, P. amnii and Peptoniphilus harei were also more frequent in the endometrium of women having endometritis (11% vs. 3%, P = 0.06) but this did not reach statistical significance. After excluding women having GC and/or CT, A. vaginae was still independently associated with endometritis (17% vs. 3%, P = 0.03). Conclusions: The recovery of non STIs from the endometrium is associated with histologic endometritis among women with clinically diagnosed PID. A. vaginae may play an etiologic role in PID and merits further evaluation for its role in nongonococcal/nonchlamydial PID.